Imperial Technology and 'Native' Agency A Social History of Railways in Colonial India, 1850-1920 - Mukhopadhyay, Aparajita (Taylor & Francis, 2017)
This book explores the impact of railways on colonial Indian society from the commencement of railway operations in the mid-nineteenth to the early decades of the twentieth century.The book represents a historiographical departure. Using new archival evidence as well as travelogues written by Indian railway travellers in Bengali and Hindi, this book suggests that the impact of railways on colonial Indian society were more heterogeneous and complex than anticipated either by India's colonial railway builders or currently assumed by post-colonial scholars.